A HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY-MASS SPECTROMETRY METHOD DEVELOPMENT FOR THE QUANTITATIVE DETERMINATION OF ENALAPRIL MALEATE FROM CACO-2 CELL MONOLAYERS - Logoyda, Liliya (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: A simple, rapid high-performance liquid chromatography-mass spectrometry (HPLC MS/MS) method was developed for the determination of enalapril maleate from confluent Caco-2 monolayers and aqueous solution. Methods: Chromatography was achieved on Discovery C18, 50Ã—2.1 mm, 5 Î¼m column. Samples were chromatographed in a gradient mode (eluent A [acetonitrile-water-formic acid, 5: 95:0.1 v/v] and eluent B [acetonitrile-formic acid, 100:0.1 v/v]). The initial content of the eluent B is 0%, which increases linearly by 1.0 min to 100% and 1.01 min returns to the initial 0%. The mobile phase was delivered at a flow rate of 0.4 ml/min into the mass spectrometer ESI chamber. The sample volume was 5 Î¼l. Results: Under these conditions, enalapril maleate was eluted at 1.52 min. According to the Caco-2 test results, enalapril showed low permeability. It should be noted that the recovery value for enalapril is 100.62 %. Low in vitro permeability data for enalapril are in good agreement with the literature data. Conclusion: From results of the analysis, it can be concluded that developed method is simple and rapid for determination of enalapril maleate from confluent Caco-2 monolayers and aqueous solution. Acquired results demonstrate that proposed strategy can be effortlessly and advantageously applied for examination of enalapril from Caco-2 cell monolayers.